2011
DOI: 10.1645/ge-2620.1
|View full text |Cite
|
Sign up to set email alerts
|

Description of Adults and Nymph, and Redescription of the Larva, of Ornithodoros marinkellei (Acari: Argasidae), with Data on Its Phylogenetic Position

Abstract: The argasid tick Ornithodoros marinkellei Kohls, Clifford, and Jones, 1969 was described 4 decades ago based on larval specimens collected from bats (Pteronotus spp.) in Colombia and Panama. Thereafter, larval O. marinkellei parasitizing bats were reported from Venezuela, Guyana, and Brazil. Herein, we describe the adults and nymph, and redescribe the larva of O. marinkellei based on specimens recently collected in the western Brazilian Amazon region. In contrast to all other known adult argasids, the idiosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 16 publications
1
27
0
2
Order By: Relevance
“…Although a detailed description of the larvae from both species has not been published, morphological characters of Antricola larvae presented by Cooley & Kohls (1944), and posteriorly by Kohls et al (1965), coincide with the general morphology of the larva found parasitizing P. parnelli in the present study. This host-parasite association is not unexpected since both Antricola and Pteronotus bats live in caves (ESTRADA-PEÑA et al, 2004;GUIMARÃES & FERREIRA, 2014;LABRUNA et al, 2011), and because Antricola larvae have been reported on Pteronotus bats in the Amazon biome (LABRUNA et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Although a detailed description of the larvae from both species has not been published, morphological characters of Antricola larvae presented by Cooley & Kohls (1944), and posteriorly by Kohls et al (1965), coincide with the general morphology of the larva found parasitizing P. parnelli in the present study. This host-parasite association is not unexpected since both Antricola and Pteronotus bats live in caves (ESTRADA-PEÑA et al, 2004;GUIMARÃES & FERREIRA, 2014;LABRUNA et al, 2011), and because Antricola larvae have been reported on Pteronotus bats in the Amazon biome (LABRUNA et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…This soft tick was described from free-living specimens from caves in the Caatinga biome, and from bat-associated larvae in the Cerrado Biome of central-western Brazil (DANTAS-TORRES et al, 2012 In Brazil, O. marinkellei was previously reported in caves from eastern (LABRUNA et al, 2011) and western (HENRIQUE-SIMÕES et al, 2012) Amazonian biome, in association with three bat species of the genus Pteronotus (LABRUNA et al, 2011). In this way it is not surprising that in the current study larval stages of this tick (KOHLS et al, 1969;JONES & CLIFFORD, 1972;VENZAL et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations